Determinants of Tax Avoidance in Indonesian Conventional Banks Listed on the IDX - Henri, H.; Puspitasari, Elen (Golden Ratio of Taxation Studies, 2026)
This study investigates the determinants of tax avoidance in conventional commercial banks listed on the Indonesia Stock Exchange (IDX) during 2016–2024. Tax avoidance poses significant challenges to fiscal sustainability in emerging economies, particularly within highly regulated sectors such as banking. While prior studies primarily focus on general corporate characteristics, limited research integrates banking-specific prudential indicators into tax behavior analysis. Addressing this gap, this study examines the effects of profitability, leverage, firm size, audit quality, fixed asset intensity, and Capital Adequacy Ratio (CAR) on tax avoidance. Using purposive sampling, 24 banks were selected, generating 216 firm-year observations. Tax avoidance is proxied by Cash Effective Tax Rate (CETR), where a higher CETR reflects lower tax avoidance. Employing panel data regression analysis based on secondary financial statement data, the results reveal that leverage (DER), firm size, audit quality, fixed asset intensity, and CAR significantly influence tax avoidance, while profitability (ROA) shows no significant effect. Leverage, firm size, audit quality, and CAR negatively affect CETR, indicating higher tax avoidance, whereas fixed asset intensity positively affects CETR, indicating lower tax avoidance. These findings contribute to agency theory by incorporating regulatory capital considerations into corporate tax behavior analysis and provide practical implications for regulators in strengthening governance and tax compliance within the banking sector.